Relationships Attitudes, Role of Parents, and The Community Environment With Knowledge about HIV/AIDS in Adolescents - siswosuharjo, partono; Avenzoar, H. Nur Avenzoar; Qohar, Abdul (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Cases of STI (Sexually Transmitted Infections) and HIV / AIDS are quite common among adolescents. Various types of STIs and HIV / AIDS are very influential on a person's health level in general and reproductive health conditions in particular because in general, various STI and HIV / AIDS infections are directly related to the human reproductive system. Even HIV / AIDS can have an impact on death. The purpose of this study was to determine the factors related to knowledge of HIV / AIDS in adolescents. This research is an analytical survey research in which the research will be conducted is a research using cross sectional research method (cross-cutting) because in this study the independent and dependent variables will be observed at the same time. Based on the results of the study, it can be concluded that the distribution of adolescent knowledge about HIV / AIDS at SMK Gema Gawita Tangerang in 2019, namely Not Good as many as 54 respondents (58.7%) and Good as many as 38 respondents (41.3%). The distribution of adolescent knowledge about HIV / AIDS based on gender was 46 respondents (50%) and 46 respondents (50%), based on The role of parents were 60 respondents (65.2%) and 32 respondents (34.8%) had a role. %), based on the Attitude of students who have negative Attitude as many as 45 respondents (48.9%) and positive ones as many as 47 respondents (51.1%), based on the environment where there are as many as 24 respondents (26.1%) and those who support 68 respondents (73.9%), based on Information Technology, there were 31 respondents (33.7%) and 61 respondents (66.3%) made use of it.